AIR POLLUTANTS IN FOOD PROCESSING PLANTS IN IRAN - F. Akbarkhanzadeh; P. Meshgi (Tehran University of Medical Sciences, 1979)
Investigations have been carried out on the indoor air pollution in .different workshops of food processing plants in Iran. In order to evaluate the exposure of workers to the three most commonly used indices of air pollution ten food processing plants representing ten groups of food industry with 2.816 workers were selected. Air borne contamination of different origins such cotton seed. Barley, wheat flour salt and different spices sugar an1 beans dust were measured in 237, work places. Here contamination was 8-9 times higher than the proposed T.L. V. for in.3rt dust in 12% of sampling sites Carbon monoxide, measured in 94 sampling site in 69 different work places, which was higher than 50 P .P.M1. in 13% of samples and sulfur-bearing air pollutants determined in 87 different workshop where 103 samples were collected showed the existence of oxides of' sulfur in 34 samples in six industries. The results are presented and the reasons of the existence of these air pollutants are discussed.